A Method for Estimation of Traffic States Considering Floating Car Data in a Large Network - DUAN, Kaifeng; TANI, Ryuichi; UCHIDA, Kenetsu; ZUSHII, Keita; NAGAOKA, Osamu (Journal of the Eastern Asia Society for Transportation Studies, 2024)
This study proposes a computationally efficient method for the traffic states estimation by using floating car data. The traffic states in a road network are obtained by solving a full information maximum likelihood estimation (FIMLE) problem under user equilibrium (UE) constraints. Solving the FIMLE problem under UE constraints requires much computations time. Therefore, a solution algorithm based on the sensitivity analysis for UE is proposed in this study. We estimate the traffic states in the Asahikawa network in Hokkaido, Japan by applying the method proposed in this study.